2014
DOI: 10.2108/zs130201
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships, Genetic Divergence, Historical Biogeography and Conservation of an Endangered Gecko,Goniurosaurus kuroiwae(Squamata: Eublepharidae), from the Central Ryukyus, Japan

Abstract: The Kuroiwa's eyelid gecko Goniurosaurus kuroiwae is an endangered species in a state of relict endemism in the Central Ryukyus, Japan, and is divided into five subspecies. We analyzed variations in sequence data for approximately 1900 base positions of mitochondrial 12S and 16S rRNA, and cytochrome b genes from samples representing all recognized subspecies of G. kuroiwae together with those from congeneric species in order to test the relevant previous phylogenetic hypotheses and discuss biogeographical impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 80 publications
4
34
0
1
Order By: Relevance
“…This hypothesis, which we term the Pre‐Pleistocene Isolation (PPI) hypothesis, predicts that lineages from Ryukyu may have been the first to diverge, and that lineages from southern islands and Taiwan should be younger and more recently derived. Kizaki & Oshiro () have suggested a similar hypothesis based on their reconstruction of the land mass connection; empirical evidence congruent with the PPI hypothesis (diversification before the Pleistocene) had been reported from terrestrial organisms such as reptiles (Honda et al ., ), amphibians (Matsui et al ., ), and insects (Maekawa et al ., ). However, explicit investigations of the PPI hypothesis were not emphasized in those earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis, which we term the Pre‐Pleistocene Isolation (PPI) hypothesis, predicts that lineages from Ryukyu may have been the first to diverge, and that lineages from southern islands and Taiwan should be younger and more recently derived. Kizaki & Oshiro () have suggested a similar hypothesis based on their reconstruction of the land mass connection; empirical evidence congruent with the PPI hypothesis (diversification before the Pleistocene) had been reported from terrestrial organisms such as reptiles (Honda et al ., ), amphibians (Matsui et al ., ), and insects (Maekawa et al ., ). However, explicit investigations of the PPI hypothesis were not emphasized in those earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…() and Honda et al. () studied the molecular phylogenetic pattern of G. kuroiwae and observed large genetic divergence between G. k. kuroiwae from the northern and southern parts of Okinawajima, as well as the closer genetic affinity of the latter with G. k. orientalis from Iejima. Honda et al.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the Ryukyu Goniurosaurus is considered to be a relict endemic along with several other terrestrial vertebrates in the Central Ryukyus (Ota, ). Within the Central Ryukyus, there is considerable genetic and morphological differentiation among the islands (Grismer et al., ; Honda, Kurita, Toda, & Ota, ; Honda & Ota, ; Ota, Honda, Kobayashi, Sengoku, & Hikida, ), with the most prominent divergence between Tokunoshima in the Amami Islands Group and the remaining 10 islands in the Okinawa Islands Group (Honda et al., ). Thus, six allopatric taxa are currently recognized as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herpetofaunal surveys in northern Vietnam and southern China resulted in the discovery of eight new Goniurosaurus species in the past two decades (Grismer et al 1999(Grismer et al , 2002Orlov et al 2008;Ziegler et al 2008;Wang et al 2010Wang et al , 2013Wang et al , 2014, and in a phylogenetic study of Goniurosaurus species in the Ryukyu Archipelago, Honda et al (2014) reported the presence of two undescribed taxa within the Goniurosaurus kuroiwae species group; these studies indicate species diversity of the genus Goniurosaurus is still underestimated. Based on morphological and phylogenetic studies, 15 taxa within four major species groups are widely recognized at present (Grismer et al 1999(Grismer et al , 2002Honda et al 2014;Wang et al 2013Wang et al , 2014: (1) The first record of the genus Goniurosaurus from Guangxi was reported by Wen (1983), which was identified as "G. lichtenfelderi" in all early accounts of the genus from China (Li et al 1995;Zhao & Adler 1993;Zhao et al 1999). But it is now believed that G. lichtenfelderi only occurs in northern Vietnam (Ziegler et al 2008;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%